From “Confucian Orthodoxy” Discourse to Neo-Confucianism and The Four Books - Chanthsithiporn, Sayumporn (Journal of Sinology (วารสารจีนวิทยา), 2013)
This article aims to point out the relation of the formation of the discourse “Confucian orthodoxy” (道统) to Neo-Confucianism (理学) and The Four Books《四书》. The study found that this relation has been considered as historical and philosophical development of Chinese society caused by the Confucianism movement, which was weakened by both internal and external factors. The “Confucian orthodoxy" discourse was an important process that leading to certain changes. Neo-Confucianism was the effect of the paradigm shift from Confucianism, and The Four Books is the important product of this process.